MODEL OF SUPPORT DESIGN DECISIONS IN THE DESIGN OF GLAZING ON THE BASIS OF "INDIVIDUAL CUSTOMER DATA" - Lisnevskyi, R. V. (Science and Transport Progress, 2005)
The article gives estimation to the task of development and introductions of the decisions support systems in the process of designing glass packages. The forecasts have been made of sharpening of contradictions, characterizing the process of designing; submitted for consideration is an approach to solving the task of informational simulation of the process of making design solution in designing the glass packages in building constructions on the basis of «individual requirements of customer», which is presented in the form of mathematical setting of decision-making task and general sequence of its solution. Realization of the proposed approach will allow not only to improve the quality of project decisions in particular, but to increase efficiency of designing glass packages in building constructions in general.